An Experimental Investigation on the Microscopic Damage and Mechanical Properties of Coal Under Hygrothermal Conditions - Haisen Zhao; Guichen Li; Jiahui Xu; Yuantian Sun; Fengzhen He; Haoran Hao; Mengzhuo Han; Bowen Tian (Applied Sciences, 2025)
Investigating the microstructural damage and mechanical properties of coal under deep mine hygrothermal conditions is essential for ensuring the safe and efficient extraction of coal resources. In this study, X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), and nanoindentation techniques were employed to examine the surface morphology and microscale mechanical properties of coal samples exposed to four environmental conditions, initial, humidified, heated, and coupled hygrothermal, under a peak indentation load of 70 mN. The results indicate that humidification led to the formation of dissolution pores and localized surface softening, resulting in a 15.9% increase in the peak indentation depth and reductions in the hardness and elastic modulus by 29.53% and 17.14%, respectively. Heating caused localized disintegration and the collapse of the coal surface, accompanied by surface hardening, with a slight 0.4% decrease in the peak indentation depth and increases in hardness and the elastic modulus by 1.32% and 1.56%, respectively. Under the coupled hygrothermal condition, numerous fine dissolution pores and microcracks developed on the coal surface, and the mechanical properties exhibited intermediate values between those observed in the humidified and heated states. Notably, the elevated temperature suppressed the moisture penetration into the coal matrix to some extent in the hygrothermal environment. A positive correlation was found between the hardness and elastic modulus, independent of the coal sample condition. The mineralogical composition significantly influenced the microscale mechanical behavior, with hard quartz minerals corresponding to lower peak indentation depths and a higher hardness, whereas soft kaolinite showed the opposite trend.